Analisis Pemodelan Sistem Pengaduan Kasus Menggunakan Object Oriented Method (Unified Modelling Language) - Ahmad Homaidi; Syahrul Ibad (Jurnal Ilmiah Informatika, 2019)
This complaint system implemented at the Bondowoso District Inspectorate uses the form stipulated in the regent's regulation. In this system what is done is that the party making the complaint fills out the form by bringing evidence related to the reporting and must go to the Bondowoso Inspectorate office both this complaint individually or from an institution or non-governmental organization. The advantage of this system is that the inspectorate can interact directly with the party making the complaint so that when there is something less clear about the complaint, it can be asked directly to the applicant. But apart from all the advantages of the current system, the inspectorate still has to make a good inventory of complaints files, not to mention making assignments that must be done with a manual system so that it takes more time and takes up space. To overcome these problems, the authors feel the need to do an analysis to model the complaints system so that later the making of the complaints system can be well structured and meet the general description of the system needed. The design of this complaints system uses an object oriented method that can describe the behavior of objects related to the system. From the results of this modeling it was found that the complaints system modeling can accommodate problems that have occurred so far and facilitate the interaction of the reporter and the handling of reported cases.